Cavitation Process and the Performance of Some Ferrous and Non-Ferrous Alloys (Iranian Journal of Chemical Engineering)
"> In this research an extensive literature search into the mechanism of cavitation dynamics and its consequences was conducted. A cavitation venturie rig was designed and constructed, and the cavitation number was checked mathematically. A new camera technique was developed to capture the cavitation cloud. Carbon steel (AISI 1020), stainless steel (AISI 304 and 316), ferritic alloy steel (B1274), brass (C27000), phosphor bronze (C51000) and aluminum bronze (C60800) test pieces were prepared and tested in the venturie tube. Aluminum bronze was the most and carbon steel the least resistant of these alloys, the measured mechanical properties could not systematically be correlated with cavitation resistance. The microscopic examinations showed that cavitation induced plastic deformation had caused the misalignment of polishing lines. A field study into the susceptibility of an Iranian sugar cane company’s centrifugal pumps showed that deviation from the manuals hydraulic settings caused cavitation and that the gray cast iron had a poor resistance. Besides the venturie tube, other configurations were considered, of which an oil industry choke valve was constructed and examined for cavitation.